2020
DOI: 10.14444/7045
|View full text |Cite
|
Sign up to set email alerts
|

Does Type II Diabetes Induce Early Senescence and Degeneration in Human Intervertebral Discs? A Tissue Biomarker Evaluation

Abstract: Background: Diabetes mellitus is one of the leading causes of morbidity resulting in multi-organ dysfunction. Animal studies have shown that hyperglycemia results in stress-induced senescence through the p16-pRb pathway, thereby accelerating early disc degeneration. There is a paucity of literature on the effect of hyperglycemia in human intervertebral disc cells. We aimed to analyze the effect of diabetes mellitus in human intervertebral disc cells. Methods: This is a prospective study done in patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…During in vivo investigations, STZ + NA and HFD-induced DM mice showed structural malformation of IVD, in the terms of narrowed disc height and highly reduced levels of chondrogenic markers including SOX9, type 2 collagen and aggrecan at gene and protein levels, representing IVDD. These results are in line with a prospective study of 24 patients, T2DM hastened stress-induced deformed NP with clustered chondrocytes and enhanced cellularity, leading to IVD senescence and disc degeneration [31]. A retrospective study also concluded that prolonged T2DM and its bad control could result in severe disc degeneration [5].…”
Section: Discussionsupporting
confidence: 87%
“…During in vivo investigations, STZ + NA and HFD-induced DM mice showed structural malformation of IVD, in the terms of narrowed disc height and highly reduced levels of chondrogenic markers including SOX9, type 2 collagen and aggrecan at gene and protein levels, representing IVDD. These results are in line with a prospective study of 24 patients, T2DM hastened stress-induced deformed NP with clustered chondrocytes and enhanced cellularity, leading to IVD senescence and disc degeneration [31]. A retrospective study also concluded that prolonged T2DM and its bad control could result in severe disc degeneration [5].…”
Section: Discussionsupporting
confidence: 87%
“…Cellular senescence of IVD cells is the most important pathophysiological mechanism underlying IVD degeneration leading to IDH, and the antisenescence-based pharmacological strategies may be effective in preventing or attenuating the disease onset and progression. [123][124][125][126][127][128][129][130][131][132][133][134] The chemokine pathway is an inflammatory pathomechanism associated with IDH development and its activity is related to the generation, persistence, and severity of neuropathic and radicular pain induced by IDH; additionally, targeting this pathway may hold therapeutic potential. 122,[135][136][137][138][139] The Fork head box O (FoxO) pathway has an antioxidant effect that can protect IVDs against their degeneration induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the IL-10 gene were implicated in IVD degeneration [ 19 , 20 , 21 ]. Sudhir et al linked IVDD in diabetic patients to the production and accumulation of ROS, causing oxidative stress, DNA damage, cellular apoptosis, altered gene expressions and production of inflammatory cytokines, growth factors and degradative enzymes [ 22 ]. Heme oxygenase-1 (HMOX1) is implicated in protection against tissue injury [ 23 ].…”
Section: Introductionmentioning
confidence: 99%